FEATURES OF EMPLOYMENT OF PERSONS WITH DISABILITIES AND PERSONS WITH REDUCED WORKABILITY - Stadnichenko, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: article examines the specifics of employment of persons with disabilities and persons with reduced working capacity. It is emphasized that the employment of these categories of citizens is an important aspect of their social and economic integration. The article defines the basic rights of persons with disabilities and persons with reduced working capacity in the field of work, as well as the specifics of employment of this category of citizens. The article also discusses measures that can contribute to increasing the level of employment of persons with disabilities and persons with reduced working capacity. To investigate the current state of social reforms and their impact on social security in Ukraine, in particular, paying attention to European social standards as potential guidelines for the newest model of sources of social security law. Research methods: the research is based on the analysis of modern studies in the field of social reforms and uses methods of evaluation and comparative analysis. European experience and practice are studied as key components to understand the best ways to improve social security. Results: the study found that it is necessary to study and implement European social standards in more detail to solve the problems of efficiency, accessibility and inclusiveness of the Ukrainian social security system. Analysis of current trends in social reforms provides important guidelines for further improvements. Discussion: the discussion is aimed at determining specific measures to improve social security in Ukraine based on European standards. The need for a deeper study and adaptation of best practices to increase the efficiency and inclusiveness of the system is indicated. This article is distinguished by its focus on the practical application of European experience in the context of Ukrainian social reforms, creating a basis for further discussions and improvements in the field of social security in Ukraine. The conclusion of the article is that employment of persons with disabilities and persons with reduced working capacity is an important task for society. To solve it, it is necessary to ensure the observance of the rights of this category of citizens in the field of work, as well as to develop and implement effective measures for their employment.